Math-gender stereotypes and career intentions: an application of expectancy–value theory. Issue 3 (27th May 2017) - Song, Jingjing; Zuo, Bin; Wen, Fangfang; Yan, Lei
ABSTRACT: Exposure to negative math-gender stereotypes undermines the intentions of female college students to engage in careers in the math field, yet the mechanisms by which such stereotypes relate to girls' career intentions remain unclear. We simultaneously tested multiple mediators in a sample of 186 female students from one high school in central China. Participants completed five questionnaires that measured mathematics-related gender stereotypes, competence beliefs, task value, sexual attraction beliefs and career intentions. The path analysis results indicated that math-gender stereotypes were negatively related to adolescent girls' career intentions in math fields through negative relationships with students' mathematics-related competence beliefs, task value and sexual attraction beliefs. These results are discussed in terms of their implications for theory and educational practice.